PENANAMAN JIWA BIJAK MENGELOLA UANG PADA SISWA PAUD KELURAHAN SIWALANKERTO SURABAYA MELALUI KEGIATAN SERVICE LEARNING MATA KULIAH PERSONAL FINANCE - Nanik Linawati (SHARE: Journal of Service Learning, 2015)
Golden opportunity will not be repeated twice. This applies to the future development of early childhood education students (PAUD) who are at the Golden Period. During this learning period is very important, as it will also determine the direction of mental development of children at a next stage. Teach the wisdom to manage money through savings habits will become one of the pillars that sustain the child in the future when they are growing up. The involvement of higher education students in the activities of Service Learning is one of the precious moments for the students, because these activities give students the opportunity to share their knowledge and part of their funds to the community, especially the students of early childhood education (PAUD), learn to socialize with different strata of society, learn the meaning of dedication from Bunda PAUD who teach the children from low income family without expecting reward.